TINJAUAN HUKUM ISLAM TERHADAP PERUBAHAN PERAN EKONOMI KELUARGA KORBAN BANJIR BANDANG DALAM PEMBENTUKAN KELUARGA SAKINAH DI DESA RADDA BAEBUNTA LUWU UTARA - Zulayka Muchtar; Hartini Tahir; Rahma Amir (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
The main problem in this study is how to review Islamic law on changes in the economic role of the families of victims of the flash flood disaster in forming a Sakinah family in Radda Village. This research is field research that is described qualitatively using normative-juridical legal studies and syar'i, philosophical, sociological, and psychological approaches. The results of the study show that the views of the victims of the Radda flash flood disaster regarding a Sakinah family are that it is a family that is happy, harmonious, full of affection for fellow family members, and that religious values are instilled in the family to run the family and are always committed to being together in changing circumstances. The view of Islamic law on changes in the economic role of the family is that, first, children helping support the family is permissible as a form of good deed for both parents. Second, the wife helping support the family is permissible as long as she continues to follow the Shari'a. Third, the husband's not working is a sinful act because he neglects his obligations without any elements that allow him to not carry out these obligations.